2014
DOI: 10.21236/ada616690
|View full text |Cite
|
Sign up to set email alerts
|

Localized Tissue Surrogate Deformation due to Controlled Single Bubble Cavitation

Abstract: Cavitation-induced shock wave, as might occur in the head during exposure to blast waves, was investigated as a possible damage mechanism for soft brain tissues. A novel experimental scheme was developed to visualize and control single bubble cavitation and its collapse, and the influence of this process on a nearby tissue surrogate was investigated. The experiment utilized a Hopkinson pressure bar system which transmits a simulated blast pressure wave (with over and under pressure components) to a fluid-fille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…As the shockwave scatters from the proximal cloud surface, a new section of the cloud is generated with each cycle. Shockwave-induced cavitation (SIC), a broad subsection that includes AIC, techniques include drop tower (41), Split-Hopkinson or Kolsky bar (4,8), and controlled blast (87) setups. Confinement-induced cavitation.…”
Section: A B Cmentioning
confidence: 99%
“…As the shockwave scatters from the proximal cloud surface, a new section of the cloud is generated with each cycle. Shockwave-induced cavitation (SIC), a broad subsection that includes AIC, techniques include drop tower (41), Split-Hopkinson or Kolsky bar (4,8), and controlled blast (87) setups. Confinement-induced cavitation.…”
Section: A B Cmentioning
confidence: 99%
“…during brain injury, a number of challenges have impeded the controlled study of these bubbles in viscoelastic media. In particular, generating single, spherical bubbles at precisely controlled locations using transient acoustic pulses [8,34] is difficult to accomplish without modifying the media, for example, by injecting gas microbubbles or inserting point defects in the media [35].…”
Section: Introductionmentioning
confidence: 99%
“…These results, along with several other experiments on human brain surrogates of ranging realism demonstrating the existence of cavitation at pressures around -1 atmospheres (or roughly -100 kPa), are pointing to suggestive evidence that microcavitation might indeed be a possible injury mechanism of not just blast but also possibly blunt head trauma [13,20,22,23]. Works by several groups have shown that pressures near the estimated cavitation threshold of -1 atmosphere can be generated in head impacts sustained from sports-related or vehicular incidents, even in the absence of an explosive pressure wave [24,25].…”
mentioning
confidence: 60%
“…However, increasing mounting evidence, in particular in the last few years, has provided us with a better understanding that inertial microcavitation in the brain might indeed be a real possibility [13,20–23]. For example, Goeller  et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation